Mapping and morphometric analysis of synapses and spines on fusiform cells in the dorsal cochlear nucleus - Salloum, Rony H.; Chen, Guoyou; Velet, Liliya; Manzoor, Nauman F.; Elkin, Rachel; Kidd, Grahame J.; Coughlin, John; Yurosko, Christopher; Bou-Anak, Stephanie; Azadi, Shirin; Gohlsch, Stephanie; Schneider, Harold; et al. (Frontiers in Systems Neuroscience, 2014)
Fusiform cells are the main integrative units of the mammalian dorsal cochlear nucleus (DCN), collecting and processing inputs from auditory and other sources before transmitting information to higher levels of the auditory system. Despite much previous work describing these cells and the sources and pharmacological identity of their synaptic inputs, information on the 3- dimensional organization and utltrastructure of synapses on these cells is currently very limited. This information is essential since an understanding of synaptic plasticity and remodeling and pathologies underlying disease states and hearing disorders must begin with knowledge of the normal characteristics of synapses on these cells, particularly those features that determine the strength of their influence on the various compartments of the cell. Here, we employed serial block face scanning electron microscopy (SBFSEM) followed by 3D reconstructions to map and quantitatively characterize synaptic features on DCN fusiform cells. Our results reveal a relative sparseness of synapses on the somata of fusiform cells but a dense distribution of synapses on apical and basal dendrites. Synapses on apical dendrites were smaller and more numerous than on basal dendrites. The vast majority of axosomatic terminals were found to be linked to other terminals connected by the same axon or different branches of the same axon, suggesting a high degree of divergent input to fusiform cells. The size of terminals was correlated with the number of mitochondria and with the number of active zones, which was highly correlated with the number of postsynaptic densities, suggesting that larger terminals exert more powerful influence on the cell than smaller terminals. These size differences suggest that the input to basal dendrites, most likely those from the auditory nerve, provide the most powerful sources of input to fusiform cells, while those to apical dendrites (e.g., parallel fiber) are weaker but more numerous.